A Method To Support The Adoption of Reuse Technology in Large Software Organizations - Amorim, Luiz Augusto Matos de (2016)
The process of adopting a software technology in a large organization is significantly influenced by organizational culture and behavioral aspects of the practitioners involved in the process. The identification of factors that will facilitate or hinder this process is strongly correlated with the existing system of beliefs and represents a key element to the planning of this process. The adoption of software reuse technology in particular significantly alters the software process of the organization as well as the modus operandi of the involved practitioners. Our aim is to propose an action model based on classes of beliefs that will support the process of adoption of software reuse technology, providing a means to deal with beliefs that may hinder the adoption process. A case study was conducted in a large organization to validate and refine the proposed method. As a result of this work, we propose a method based on the identification of classes of beliefs and re-signification of those that hinders the adoption of software reuse technologies. Also is provided a catalog of beliefs weighted when the impact in the technology adoption process, validated by a group of experts in the reuse area.